Mengukur kesadaran kritis: Konstruksi skala socio-political awareness for indonesian - Ahmad Sulaiman; Muhammad Fath Mashuri; Sekar Larasati Lilo Sungkono; Aliyah Zahrah; Safarina Firdausi Royhana (Fakultas Psikologi, 2022)
Critical awareness has recently become a widely studied topic in the intellectual, social and educational scientific community. The concept that was coined by the Brazilian critical educator is considered important because it covers a crucial aspect of consciousness that is often forgotten. Researches that seek to increase critical awareness have begun to be carried out, but they are not supported by a standardized measurement instrument. This causes the validity of the research results to be questioned. It is only in the last five years that efforts to construct critical awareness instruments have received attention. This study will construct a critical awareness scale for the Indonesian population called the Socio-Political Awareness Scale for Indonesian (SPASI). The scale refers to the concept of critical consciousness proposed by Paulo Freire and refined by modern researchers such as Watts, Diemer, and Christensen. Three aspects of critical awareness used in this scale include Social-Dominance, Critical Reflection and Socio-Political Action. The results of the analysis show that the eleven items on the SPASI scale have reliability and validity scores that meet the requirements. Keywords: critical consciousness, Paulo Freire, scale construction